Islam at the Tropenmuseum (LM Publ., 2014)
This is the fifth volume of a series of ten books that discuss the collections of the Tropenmuseum and the histories and stories that accompany them. The books elucidate the often hidden backgrounds of a museum collection, discussing objects within their original context, social histories and their contemporary meaning. The main emphasis lies on the history of each collection, with its different collecting and presentation practices placed in a particular time and place. Each volume is richly illustrated with objects and photographs from the Tropenmuseum collection